Manager’s competence model in the face of new economic challenges – research report - Igielski Michał (Management)
The main aim of the article is to try to determine, on the basis of the conducted research, the optimal competencies and skills that a manager should have in order to effectively manage the team (in the opinion of its members). The author will also indicate the connection and differences between the obtained data resulting from the Polish reality and the contemporary guidelines for the IPMA competence model. Apart from literature analysis, the author chose a diagnostic survey (research technique - questionnaire) as another research method. The respondents were, in 2019, employees (who agreed to take part in the survey) from 14 deliberately selected large enterprises based in Poland (200 people in total took part in the research process). After the analysis of the literature and the results of the conducted research, of course bearing in mind its pilot character, we can see that the perception of the competencies and skills of a manager, in Poland, is not fundamentally different from the model of competencies presented in the content. The only question that remains is whether this will be enough to bridge the gap between Poland and developed countries, especially in the face of new economic challenges.